Rhetorical Mixture: Hermogenes and Hybridity in English Renaissance Literary Criticism - Javiera Lorenzini Raty (Sillages Critiques)
Hermogenes of Tarsus’ innovative stylistic theory is arguably the most neglected, yet most influential rhetorical source of stylistic and generic hybridity in Renaissance England. His treatise On Ideas of Style (Περὶ ἰδεῶν) presented mixture both as a quality of all styles, and also as a core value of dignified styles, encouraging writers to compose hybrid texts and to read the literary tradition with attention to its combination of forms. This article shows the pervasive reception of his theory in vernacular literary criticism composed in England in the sixteenth and early seventeenth centuries, as well as their main continental antecedents. It argues that Hermogenes was both a key and controversial source of the mixed styles of the period – styles that transgressed the boundaries of poetic decorum and which were embodied in emergent hybrid forms such as tragicomedy or epyllion. Through an examination of work by scholars and poets such as George Puttenham, George Chapman, William Scott, and William Carew, this article demonstrates that Hermogenes both shapes and sheds light on these authors’ main discussions on literary hybridity, informing alternative and radical understandings of poetic form.